Strategi Pengembangan Potensi Obyek Wisata Pulau Sanrobengi Kabupaten Takalar - Muhammad Idris Taking; Ayensi Mokoginta; Rudi Latief (Journal of Urban Planning Studies, 2021)
The purpose of this study is to identify the factors that influence the development of the Sanrobengi Island Tourism Object, Takalar Regency. As well as to find out the strategy for developing the potential of the Sanrobengi Island Tourism Object, Takalar Regency. The analytical method used is chi-square and SWOT analysis. Obtained factors that have a significant effect on the development of tourism potential of Sanrobengi Island. There are three variables that have an influence on the strategy for developing the tourism potential of Sanrobengi Island, Takalar Regency, namely tourist attraction, Tourism Support Facilities, and Accessibility. So that the strategies that can be used in the strategy of developing the potential of tourism objects on Sanrobengi Island, Takalar Regency are by socializing related to the RTRW of Takalar Regency, increasing the contribution of tourism to the quality and quantity of human resources, supporting the vision and mission of RIPPARDA and making it a reference/guideline in the development of tourism objects, increasing the power of tourism. tourist attraction by bringing back festivals / marine tourism events, Improving tourism supporting facilities and infrastructure to attract tourists / visitors, and increasing promotion by utilizing information technology.